PENGARUH KINERJA KEUANGAN DAN NILAI PASAR TERHADAP HARGA SAHAM (Studi Pada Perusahaan Yang Secara Konsisten Terdaftar Sebagai Indeks LQ45 Selama 2018-2020) - Amalia Savitri (2022)
The purpose of this study is to whether there is an effect of profitability, liquidity, leverage, and market value on stock prices because there are differences between real data and theory and there is still a research gap in previous studies. The object in this study is the LQ45 Index company for the period 2018 to 2020. The sampling method used is purposive sampling and there are 30 companies in the LQ45 Index as samples in this study Hypothesis and data analysis use data panel regression analysis by performing the Chow test, Hausman test, and Lagrange multiplier test to select the best test model to be used in this study. Based on the t-test conducted by applying a significance value of 5% or 0.05, the following results were financial performance variables using profitability, liquidity, and solvency have no effect on stock prices. Market value variables have effect on stock prices.